Utilization of artificial neural networks to resolve chemical kinetics in turbulent fine structures of an advanced CFD combustion model - Laubscher, Ryno (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.